A Survey of Exposure Level and Lifestyle Factors for Perfluorooctanoate and Perfluorooctane Sulfonate in Human Plasma from Selected Residents in Korea - Eom, Jinhee; Choi, Jaeyeon; Kim, Jiye; Kim, Yunje (MDPI, 2014)
Following few decades of commercial use, perfluorooctanoate (PFOA) and perfluorooctane sulfonate (PFOS) have been found in human blood and serum. We determined the amounts of PFOA and PFOS in human plasma (n = 183) and the effects of multiple uses of food-contact materials and smoking habits and alcohol consumption using liquid chromatography time-of-flight mass spectrometry (LC/TOF-MS). For the paper cups, the PFOA level in the plasma of the heavy user group was 1.37 times higher than that of the light user group. However, no association between the effects of multiple uses of food-contact materials and the plasma levels of PFOA and PFOS was found, except for paper cups. Active smokers had lower plasma levels of PFOA and PFOS than non-smokers. We show that multiple uses of food-contact materials do not appear to be a significant source of PFOA and PFOS.
Keywords: PERFLUORINATED COMPOUNDS; GENERAL-POPULATION